Regional cerebral blood flow, white matter abnormalities, and cerebrospinal fluid hydrodynamics in patients with idiopathic adult hydrocephalus syndrome. Issue 3 (March 1996) - Kristensen, B; Malm, J; Fagerland, M; Hietala, S O; Johansson, B; Ekstedt, J; Karlsson, T
Abstract : OBJECTIVES--(1) to evaluate regional cerebral blood flow (rCBF) with single photon emission computed tomography and 99mTc-hexamethylpropyleneamine oxime in patients with the idiopathic adult hydrocephalus syndrome (IAHS); (2) to examine regional cerebral blood flow (rCBF), gait, and psychometric functions before and after CSF removal (CSF tap test); (3) to assess abnormalities in subcortical white matter by MRI. METHODS--Thirty one patients fulfilling the criteria for IAHS (according to history and clinical and neuroradiological examination) were studied. Quantified gait measurements, psychometric testing, and rCBF before and after removal of CSF were obtained. Pressure of CSF and CSF outflow conductance were investigated with a constant pressure infusion method. Brain MRI was used to quantify the severity of white matter lesions and periventricular hyperintensities. In IAHS a widespread rCBF hypoperfusion pattern was depicted, with a caudal frontal and temporal grey matter and subcortical white matter reduction of rCBF as the dominant feature. Removal of CSF was not accompanied by a concomitant increase in rCBF. Significant white matter lesions were detected only in a minority of patients by MRI. An altered CSF hydrodynamic state with a higher CSF pressure and lower conductance was confirmed. IAHS is characterised by an abnormal CSF hydrodynamic state, associated with a widespread rCBF reduction with preference for subcortical white matter and frontal-temporal cortical regions. Furthermore in most patients MRI did not show white matter changes suggestive of a coexistent subcortical arteriosclerotic encephalopathy. At least in the idiopathic group of patients with AHS, measurements of rCBF before and after temporary relief of the CSF hydrodynamic disturbance will not provide additional information that would be helpful in the preoperative evaluation but is suggestive of a preserved autoregulation of rCBF.